Isolation of Neisseria gonorrhoeae from urine obtained by suprapubic puncture of bladders of men with gonococcal urethritis - Péc, J; Moravcík, P; Kliment, J; Fetisov, I (Genitourinary medicine, 1988)
The authors examined three urine specimens from each of 24 men with acute gonococcal urethritis. Gonococcal concentrations in urine were 7 X 10(3)/ml to 9 X 10(8)/ml in first samples, 1 X 10(2)/ml to 5 X 10(6)/ml in midstream samples, and, in the terminal samples from only 22 men, 8 X 10(4)/ml. A further 17 men with symptomless gonococcal urethritis were examined. Seven of them yielded 1 X 10(2)/ml to 2.5 X 10(5)/ml in first samples and 5 X 10(5)/ml in midstream samples, and only two yielded 5 X 10(1)/ml in final samples. All 24 men with acute gonococcal urethritis, and seven of the men with symptomless gonococcal urethritis who had yielded N gonorrhoeae in midstream urine samples, were examined by suprapubic puncture before morning voiding. Four of the 24 men with acute gonococcal urethritis were found to have infection that had ascended into the bladder.
Keywords: Urethritis; močový měchýř; Male; uretritida; Urinary Bladder; Adolescent; gonorea; Adult; odběr biologického vzorku; dospělí; mužské pohlaví; mladiství; moč; lidé; Gonorrhea; Urine; Humans; Specimen Handling; Neisseria gonorrhoeae